Kinetic model of cadmium accumulation and elimination and metallothionein response in Ruditapes decussatus - Serafim, Angela (2020)
The aim of the present study was to determine the response of metallothionein (MT) during Cd accumulation and elimination in different tissues of the estuarine bivalve Ruditapes decussatus exposed to two nominal Cd concentrations (4 and 40 microg/L) for 40 d, followed by a depuration period of 50 d. Cadmium was accumulated in all tissues of R. decussatus at both exposure concentrations, and the accumulation was tissue dependent. Use of the kinetic model showed that in the gills and remaining tissues, Cd was assimilated faster at the beginning of the exposure and decreased with time, possibly limited by the diffusion rate of this metal within the cell. In the digestive gland, however, the Cd was continuously accumulated. This could reflect that the Cd uptake rate is considerably higher than the loss rate and, therefore, that this tissue has a higher capacity to accumulate Cd compared to the other two tissues. Moreover, the application of this kinetic model in the different subcellular fractions showed that the bioconcentration factor was significantly higher in the low-molecular-weight fraction (where MT is found), suggesting that this fraction binds Cd faster, with a high uptake rate (K(u) = 32/d), and eliminates this metal more slowly (K(1) = 0.005/d). During the depuration phase, MT decreased simultaneously with Cd elimination in all tissues, although with a shorter half-life. In conclusion, the MT response prevented Cd in the tissues of R. decussatus from interfering in the normal clam metabolism; therefore, MT acts as a detoxification mechanism of Cd.